Public-private partnerships to build human capacity in low income countries: findings from the Pfizer program - Connelly Patrick; McCoy Kelly; Richards Sarah C; Vian Taryn; Feeley Frank (Human Resources for Health, 2007)
Abstract Background The ability of health organizations in developing countries to expand access to quality services depends in large part on organizational and human capacity. Capacity building includes professional development of staff, as well as efforts to create working environments conducive to high levels of performance. The current study evaluated an approach to public-private partnership where corporate volunteers give technical assistance to improve organizational and staff performance. From 2003 to 2005, the Pfizer Global Health Fellows program sent 72 employees to work with organizations in 19 countries. This evaluation was designed to assess program impact. Methods The researchers administered a survey to 60 Fellows and 48 Pfizer Supervisors. In addition, the team conducted over 100 interviews with partner organization staff and other key informants during site visits in Uganda, Kenya, Ghana, South Africa and India, the five countries where 60% of Fellows were placed. Results Over three-quarters of Fellowships appear to have imparted skills or enhanced operations of NGOs in HIV/AIDS and other health programs. Overall, 79% of Fellows reported meeting all or most technical assistance goals. Partner organization staff reported that the Fellows provided training to clinical and research personnel; strengthened laboratory, pharmacy, financial control, and human resource management systems; and helped expand Partner organization networks. Local staff also reported the Program changed their work habits and attitudes. The evaluation identified problems in defining goals of Fellowships and matching Organizations with Fellows. Capacity building success also appears related to size and sophistication of partner organization. Conclusion Public expectations have grown regarding the role corporations should play in improving health systems in developing countries. Corporate philanthropy programs based on "donations" of personnel can help build the organizational and human capacity of frontline agencies delivering health services. More attention is needed to measure and compare outcomes of international volunteering programs, and to identify appropriate strategies for expansion.